The Political Economy of Indonesia’s Nickel Downstreaming amid WTO Disputes and Industrial Transformation - Cik Ida Kumalasari Amirudin; Romy Hermawan (CV. Era Digital Nusantara, 2026)
Abstract: This article examines Indonesia’s nickel downstreaming policy within the interaction between global trade pressures, World Trade Organization (WTO) disputes, and domestic industrial transformation. The increasing global demand for nickel driven by the expansion of electric vehicle (EV) industries has positioned Indonesia as a strategic actor in the global mineral supply chain. However, Indonesia’s export restrictions on raw nickel ore and downstream industrial policies have generated tensions within the international trade regime, particularly through the WTO dispute initiated by the European Union. Previous studies have generally focused either on global trade governance or domestic industrial policy separately, resulting in limited integrative analysis explaining how global trade pressure, institutional capacity, and political legitimacy simultaneously shape trade policy outcomes in developing countries. Purpose: This study aims to analyze Indonesia’s nickel downstreaming policy through an integrative political economy perspective that examines the interaction between global trade governance, domestic institutional dynamics, and political legitimacy in shaping industrial transformation. Design/Methodology/Approach: This research employs a qualitative approach using policy analysis and case study methods. Data were collected from government regulations, WTO dispute documents, trade reports, investment statistics, academic journals, and secondary empirical data related to Indonesia’s nickel industry and downstream industrial development. Findings: The study finds that Indonesia’s downstreaming policy is shaped not only by global trade pressure and WTO regulations but also by domestic institutional capacity, industrial policy objectives, and economic nationalism. The policy contributed to increased processed nickel exports, industrial investment, and Indonesia’s strategic position within the global EV supply chain despite international trade disputes and external pressure from developed countries. Originality/value: This article contributes to the literature by developing an integrative analytical framework that explains how global trade governance, domestic institutional capacity, and political legitimacy interact in shaping industrial policy outcomes.